Levelling the Global Playing Field through Optimal Non-Discriminatory Corporate Taxes and Subsidies - Antonella Nocco; Gianmarco Ottaviano; Matteo Salto; Atsushi Tadokoro (Center for Economic Studies and ifo Institute (CESifo), 2024)
Due to markup distortions, in international trade models with monopolistic competition and heterogeneous firms the market equilibrium is inefficient unless demand exhibits constant elasticity of substitution. When it does not, global welfare maximization generally requires policy intervention that is firm specific, and consequently of limited practical relevance due to its information requirements, discriminatory nature and susceptibility to rent seeking. We assess whether there are particular conditions under which countries can coordinate on the common use of policy tools that are not firm-specific but still maximize global welfare. We show that a demand system implying constant absolute pass-through from marginal cost to price is both necessary and sufficient for the existence of welfare-maximizing nondiscriminatory policies that can level the global playing field with a one-size-fits-all approach for all firms selling in a given market, eventually complemented by a global tax rate on corporate profits.
Keywords: D40; D60; F10; L00; L10; 330; international trade policy; firm heterogeneity; monopolistic competition; multilateralism; level playing field